机械磨损过程的在线监测 - 管莉娜; 康晶 (Jixie chuandong)
To judge wear state of the machine,information of machine wear is acquired by collecting in lubricant.Because,abradant shows the amount of wear and information of wear stage directly.To collect abradant in oil,the abradant detection sensor was designed and tested.The means of the abradant detection and hardware/software of monitoring system of wear state are discussed.Test and usage indicate that,in oil machine wear stage can be decided by acquiring amount and rate of abradant in oil.